Inhibition of Ocular Aldose Reductase by a New Benzofuroxane Derivative Ameliorates Rat Endotoxic Uveitis. (11th November 2014) - Di Filippo, C.; Zippo, M. V.; Maisto, R.; Trotta, M. C.; Siniscalco, D.; Ferraro, B.; Ferraraccio, F.; La Motta, C.; Sartini, S.; Cosconati, S.; Novellino, E.; Gesualdo, C.; et al.
Abstract : The study investigated the effects of the aldose reductase (AR) inhibitor benzofuroxane derivative 5(6)-(benzo[ d ]thiazol-2-ylmethoxy) benzofuroxane (herein referred to as BF-5m) on the biochemical and tissue alterations induced by endotoxic uveitis in rats. BF-5m has been administered directly into the vitreous, in order to assess the expression and levels of (i) inflammatory markers such as the ocular ubiquitin-proteasome system, NF- κ B, TNF- α, and MCP-1; (ii) prooxidant and antioxidant markers such as nitrotyrosine, manganese superoxide dismutase (MnSOD), and glutathione peroxidase (GPX); (iii) apoptotic/antiapoptotic factors caspases and Bcl-xl; (iv) markers of endothelial progenitor cells (EPCs) recruitment such as CD34 and CD117. 5 μ L of BF-5m (0.01; 0.05; and 0.1 μ M) into the right eye decreased in a dose-dependent manner the LPS-induced inflammation of the eye, reporting a clinical score 1. It reduced the ocular levels of ubiquitin, 20S and 26S proteasome subunits, NF- κ B subunits, TNF- α, MCP-1, and nitrotyrosine. BF-5m ameliorated LPS-induced decrease in levels of MnSOD and GPX. Antiapoptotic effects were seen from BF-5m by monitoring the expression of Bcl-xl, an antiapoptotic protein. Similarly, BF-5m increased recruitment of the EPCs within the eye, as evidenced by CD34 and CD117 antibodies.